Exploring the Use of ChatGPT in EFL/ESL Writing Classrooms: A Systematic Literature Review - Yustinus Calvin Gai Mali (Journal of Language and Education)
Background: ChatGPT has become increasingly prevalent in higher education, particularly within EFL/ESL writing classrooms. However, the rise in plagiarism and academic dishonesty associated with its unethical use is concerning. Educational institutions must explore and design AI-use-related best practices for using generative AI technology, such as ChatGPT, more ethically in the writing classrooms.